Population and Diversity of Arbuscular Mycorrhiza Fungi in the Rhizosphere of Kasetsart Cassava Clone Grown on Two Different Locations - Rini, Maria Viva; Sitio, Selly Novita Sari; Hidayat, Kuswanta Futas (UNIVERSITY OF LAMPUNG, 2017)
Population and diversity of arbuscular mycorrhiza fungi (AMF) are varied in the soil and influenced by biotic factors such as host plant and abiotic factors such as soil fertility, soil moisture, pH, temperature, etc.Â This study aimed to determine the population, diversity, and the dominant type of AMF in the rhizosphere of Kasetsart cassava clones obtained from LampungTimur and Tulang Bawang Barat Regencies, Lampung Province, Indonesia. Population of AMF was counted directly from the rhizosphere of Kasetsart cassava clones and the diversity of AMF was assesed using a pot culture experiment.Â The results showed that the population and the diversity of AMF in the rhizosphere of Kasetsart clone obtained from Tulang Bawang Barat was higher than that from LampungTimur.Â The predominant type of AMF found in the pot culture using soil samples from Lampung Timur was spore with S2 code that belongs to the genus Gigaspora and S4 code that belongs to the genus Glomus. On the other hand, the type of AMF found in the rhizosphere of soil samples from Tulang Bawang Barat was dominated by spore with S9 code that belongs to the genus Entrophospora.